SARS-CoV-2 disease severity and transmission efficiency is increased for airborne compared to fomite exposure in Syrian hamsters - Port, Julia R.; Yinda, Claude Kwe; Owusu, Irene Offei; Holbrook, Myndi; Fischer, Robert; Bushmaker, Trenton; Avanzato, Victoria A.; Schulz, Jonathan E.; Martens, Craig; van Doremalen, Neeltje; Clancy, Chad S.; Munster, Vincent J. (Nature communications, 2021)
Transmission of SARS-CoV-2 is driven by contact, fomite, and airborne transmission. The relative contribution of different transmission routes remains subject to debate. Here, we show Syrian hamsters are susceptible to SARS-CoV-2 infection through intranasal, aerosol and fomite exposure. Different routes of exposure present with distinct disease manifestations. Intranasal and aerosol inoculation causes severe respiratory pathology, higher virus loads and increased weight loss. In contrast, fomite exposure leads to milder disease manifestation characterized by an anti-inflammatory immune state and delayed shedding pattern. Whereas the overall magnitude of respiratory virus shedding is not linked to disease severity, the onset of shedding is. Early shedding is linked to an increase in disease severity. Airborne transmission is more efficient than fomite transmission and dependent on the direction of the airflow. Carefully characterized SARS-CoV-2 transmission models will be crucial to assess potential changes in transmission and pathogenic potential in the light of the ongoing SARS-CoV-2 evolution. Here, Port and Yinda et al. directly compare the relative contribution of contact, fomite, and airborne transmission route of SARS-CoV-2 to disease outcome in Syrian hamsters; while intranasal and aerosol inoculation causes severe pathogenesis, fomite exposure is characterized by milder disease.